2021
DOI: 10.3389/fnbeh.2021.666547
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Deprivation on the Prefrontal Cortex of Male Rats: Cellular, Neurochemical, and Behavioral Outcomes

Abstract: Stressful events experienced during early life are associated with increased vulnerability of developing psychopathology in adulthood. In the present study, we exposed 9-day-old Wistar rats to 24 h maternal deprivation (MD) with the aim to investigate the impact of early life stress (ELS) on morphological, biochemical, and functional aspects of the prefrontal cortex (PFC), a brain region particularly sensitive to stress. We found that in the superficial medial orbital cortex (MO), young adult male rats had red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 101 publications
2
7
0
Order By: Relevance
“…By performing the same stress protocol as in our previous studies ( Aksic et al, 2021 ; Poleksic et al, 2021 ), we confirmed the absence of changes in PV+ cell density after MD in the IL. However, to our surprise no significant changes in the PV interneuron density were detected in the roCg1 and PrL after MD.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…By performing the same stress protocol as in our previous studies ( Aksic et al, 2021 ; Poleksic et al, 2021 ), we confirmed the absence of changes in PV+ cell density after MD in the IL. However, to our surprise no significant changes in the PV interneuron density were detected in the roCg1 and PrL after MD.…”
Section: Discussionsupporting
confidence: 85%
“…Early life stress, such as maternal deprivation, affects the curve of PNNs development in the mPFC, by prolonging the low PNNs numbers and intensity state into the adulthood, possibly preventing stabilization of projected synapses on the PV+ interneurons (Sultana et al, 2021). This view is also supported by our recent findings of increased plasticity/stability ratio, indicated by higher BNDF expression in the PFC of neonatal and young adult MD rats (Poleksic et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…According to the findings of accelerated maturation of limbic regions as a consequence of LBN and MS, it is reasonable to hypothesize a targeted increase of BDNF and IGF-1 in the cortico-limbic pathway. Two separate studies on MS-rats corroborate this hypothesis: one showing widespread cortical elevation of both BDNF and IGF-1 (Lee et al, 2012); another reporting elevated BDNF levels in the prefrontal cortex (Poleksic et al, 2021). In the amygdala, however, no significant changes in BDNF expression were observed .…”
Section: Early-life Experience Shapes the Brain During Critical Perio...mentioning
confidence: 79%